The role of Social Media in SMEs’ Customer Engagement in China - Chen, Xiunan (2017)
With the development of social media, more and more marketers use social media to engage with customers. This is due to that both development of social media is rapid and the significance of customer engagement is apparent which brings about business value. Although it could be found by prior researches that large companies tend to use social media to expand the scale of customers and attract customer to engage in social media, it is limited to investigate social media activities and have a better understanding of factors of customer engagement from the perspective of managers in the context of SMEs. In order to better understand the role of social media in SMEs’ customer engagement, this study will mainly address two research questions. This study will figure out about how SMEs use social media to engage with customers and develop customer relationship. Also, this study will try to find out the factors of customer engagement in relation to social media activities from the perspective of managers in SMEs. The research approach of case study including direct observation and interview will be conducted to collect the data and will use coding approach to analyse the data. This study will firstly observes the social media activity and then interview with 12 managers. Finally, this study suggests that SMEs use different types of strategies to attract customer engagement, including message strategy, promotion strategy and community building. It also found that there are serval drivers that encourage customer engagement from the perspective of customer-based driver and functional drivers. However, it could be notable that although social media plays an important role on the SMEs’ customer engagement, comparing with large companies, the effectiveness of social media usage is limited due to inadequate resources and few followers. Therefore, future research could investigate the difference and similarity of strategy to customer engagement in social media platform between large companies.